2014
DOI: 10.1186/1743-0003-11-154
|View full text |Cite
|
Sign up to set email alerts
|

Assessment-driven selection and adaptation of exercise difficulty in robot-assisted therapy: a pilot study with a hand rehabilitation robot

Abstract: BackgroundSelecting and maintaining an engaging and challenging training difficulty level in robot-assisted stroke rehabilitation remains an open challenge. Despite the ability of robotic systems to provide objective and accurate measures of function and performance, the selection and adaptation of exercise difficulty levels is typically left to the experience of the supervising therapist.MethodsWe introduce a patient-tailored and adaptive robot-assisted therapy concept to optimally challenge patients from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(122 citation statements)
references
References 45 publications
1
121
0
Order By: Relevance
“…In addition, Pérez-Rodríguez, et al [28] proposed a new AAN control algorithm to provide anticipatory actuation. To tailor the therapy to each patient, Metzger, et al [29] adapted exercise difficulty based on an assessment-driven selection for hand training. The focus of such adaptation algorithms is that the robot torque varies over time to continuously challenge the patient to exert his/her own effort and thus actively engage in the rehabilitation treatment [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Pérez-Rodríguez, et al [28] proposed a new AAN control algorithm to provide anticipatory actuation. To tailor the therapy to each patient, Metzger, et al [29] adapted exercise difficulty based on an assessment-driven selection for hand training. The focus of such adaptation algorithms is that the robot torque varies over time to continuously challenge the patient to exert his/her own effort and thus actively engage in the rehabilitation treatment [26].…”
Section: Discussionmentioning
confidence: 99%
“…Our VR‐based system was adaptive to the participant's PF while the participant interacted with the VR‐based tasks. Here, a cutoff score of 70% was used in tasks across different difficulty levels, similar to that used for robot‐assisted rehabilitation tasks, for outpatient clinics, and technology‐assisted skill learning . The task switching module offered tasks (chosen randomly) of varying challenges (difficulty level) based on one's PF using a state machine representation (Figure )…”
Section: System Designmentioning
confidence: 99%
“…Here, a cutoff score of 70% was used in tasks across different difficulty levels, similar to that used for robot-assisted rehabilitation tasks, for outpatient clinics, and technology-assisted skill learning. [40][41][42] The task switching module offered tasks (chosen randomly) of varying challenges (difficulty level) based on one's PF using a state machine representation (Figure 4). 43 If a participant's performance in a task belonging to a particular difficulty level was "Adequate" (≥70%; condition C1), say DL1, then our task switching module offered tasks of higher difficulty (DL2), except for DL3, because DL3 was the highest difficulty level.…”
Section: Task Switching Rationalementioning
confidence: 99%
“…Such an adaptation strategy has the potential to facilitate reinforcement learning (Naros et al, 2016b) by progressively challenging the patient (Naros and Gharabaghi, 2015). Recent studies explored automated adaptation of training difficulty in stroke rehabilitation of less severely affected patients (Metzger et al, 2014; Wittmann et al, 2015). More specifically, both robot-assisted rehabilitation of proprioceptive hand function (Metzger et al, 2014) and inertial sensor-based virtual reality feedback of the arm (Wittmann et al, 2015) benefit from assessment-driven adjustments of exercise difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies explored automated adaptation of training difficulty in stroke rehabilitation of less severely affected patients (Metzger et al, 2014; Wittmann et al, 2015). More specifically, both robot-assisted rehabilitation of proprioceptive hand function (Metzger et al, 2014) and inertial sensor-based virtual reality feedback of the arm (Wittmann et al, 2015) benefit from assessment-driven adjustments of exercise difficulty. Furthermore, a direct comparison between adaptive BRI training and non-adaptive training (Naros et al, 2016b) or sham adaptation (Bauer et al, 2016a) in healthy patients revealed the impact of reinforcement-based adaptation for the improvement of performance.…”
Section: Introductionmentioning
confidence: 99%